Formation of Students' Religious Values Through Information to Religious Activities and School Culture (Case Study at MTsN 3 Bungo Jambi) - Reksiana, Reksiana; Munawaroh, Afifah; Waedoloh, Husen (Universitas Wahid Hasyim Semarang, 2024)
The problem in this study is related to the decline in students' religious values. The purpose of this research is to describe the implementation of religious values at MTsN Bungo Jambi. This research uses a qualitative approach with explorative research. Data sources or research subjects consist of primary and secondary sources. The primary sources came from the head of the madrasah, PAI teacher and religious coordinator and several students. Meanwhile, secondary data is additional information. The data analysis technique in this study uses the Miles & Huberman data analysis technique with several stages such as data reduction, data presentation, and verification or conclusion. The validity of the data was tested by triangulating data sources to maintain the validity and validity of the research. The research found that religious values at MTsN Bungo Jambi were implemented in several habituation activities, namely: reading the Qur'an, shaking hands and saying greetings, reading prayers before and after learning, reading yasin Surahs every morning Friday, as well as tahfiz juz 30 (juz 'amma) activities. Implementation of some of these activities in fact has implications for growing the religious character of students. This implication is in line with the Ministry of Education and Culture's Strengthening Character Education (PPK) program in which the main character promoted is religious character which can be achieved through intracurricular and extracurricular activities through religious activities or habituation at school.